Effect of dried oregano as a supplement in the diet of Extremadura Blue poultry on production and reproductive parameters - Garcia-Sanchez, Alfredo; Gil, Carmen Barraso; Pardo, Francisco Maria Vazquez; Alonso, David García; Márquez-García, Francisco; Mojonero, Silvia Carretero; Suero, María del Pilar Sánchez (Revista de Ciências Agroveterinárias, 2025)
The aim of this study was to investigate the effects of 2.5% dried oregano as a source of phytoestrogens in poultry diets on reproductive performance. A total of 120 hens of the Extremeña Blue breed and 10 cocks, 43 weeks old, housed individually without air conditioning in laying cages, were randomised into two groups and given water and feed ad libitum. After 90 days of feeding, an increase in the number of eggs laid was observed in the oregano supplemented group. However, none of the other parameters studied, such as fertility and hatchability, showed any significant difference. In the same way, the semen quality parameters did not differ between the two groups studied in terms of semen concentration, semen viability, semen motility and semen abnormalities (P>0.05).